A Practical Man-In-The-Middle Attack on Signal-Based Key Generation Protocols. - Eberz, S; Strohmeier, M; Wilhelm, M; Martinovic, I (Springer, 2012)
Generating secret keys using physical properties of the wireless channel has recently become a popular research area. The main security assumption of these protocols is that a sufficiently distant adversary is unable to guess a generated secret due to the unpredictable behavior of multipath signal propagation. In this paper, we introduce a practical and efficient man-in-the-middle attack against such protocols. Using this attack, we demonstrate: (i) intentional sabotaging of key generation schemes, which leads to a high key disagreement rate, and (ii) a key recovery that reveals up to 47% of the generated secret bits. We analyze statistical countermeasures (often proposed in related work) and show that attempting to detect such attacks results in a high false positive rate, questioning the overall benefit of such schemes. We implement and experimentally validate the attacks using off-the-shelf hardware, without assuming any technological advantage for the adversary. © 2012 Springer-Verlag.